Insights on the enigmatic millipede order Siphoniulida (Myriapoda, Diplopoda): a new species bearing ozopores and its phylogenetic implications - Recuero,Ernesto; López-Estrada,E. Karen; Harden,Curt W. (PeerJ, 2026)
The millipede order Siphoniulida is one of the most enigmatic and rare groups within Diplopoda, with fewer than 10 complete specimens known from two extant species and two amber fossils. This study presents the discovery of a new species, Siphoniulus porosus sp. nov., from a tropical montane cloud forest in Veracruz, Mexico, representing the highest elevation record for the order in the New World. We obtained the first molecular data for the order, a DNA barcode sequence of the Cytochrome C Oxidase I (COI). Detailed morphological analysis using scanning electron microscopy (SEM) showed that, unlike previously described species, Siphoniulus porosus sp. nov. exhibits ozopores, challenging the current understanding that Siphoniulida lack these structures. Phylogenetic analyses using both Maximum Parsimony and Bayesian methods were conducted, including a reassessment of existing morphological data considering the presence of ozopores in Siphoniulida as the ancestral state for this character. The results suggest a phylogentic position within the subterclass Eugnatha, though relationships in this group are not resolved. This discovery indicates a potentially greater diversity of Siphoniulida in the Neotropical Region and highlights the need for further exploration of montane cloud forests to discover additional species.
Keywords: Taxonomy; Phylogeny; Morphology; Montane cloud forest; Cytochrome C Oxidase I; Helminthomorpha; Dark taxa